Probiotics and Prebiotics (Journal of Chittagong Medical College Teachers' Association, 2013)
Thousands of species of bacteria colonize gut. The number of microbes is ten times that of total human body cells. The intestinal microbiota is not always harmful, sometimes it is beneficial for human health. If the growth and activity of the intestinal microbiota is perturbed, it may lead to various diseases such as irritable bowel syndrome, autoimmune diseases, infections, colon cancers, gastric ulcers, cardiovascular disease and obesity. Restoration of the gut microbiota may be done by the use of probiotics (beneficial bacteria). Prebiotics, on the other hand, are the food substrate for probiotics. This review article describes uses and harms of probiotics and prebiotics in the body and their rationale for using in diet.JCMCTA 2012 ; 23 (2): 62-68